2007
DOI: 10.1128/mcb.01097-07
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Scaffold of Pre-snoRNP Factors Facilitates Human Box C/D snoRNP Assembly

Abstract: The box C/D small nucleolar RNPs (snoRNPs) are essential for the processing and modification of rRNA. The core box C/D proteins are restructured during human U3 box C/D snoRNP biogenesis; however, the molecular basis of this is unclear. Here we show that the U8 snoRNP is also restructured, suggesting that this may occur with all box C/D snoRNPs. We have characterized four novel human biogenesis factors (BCD1, NOP17, NUFIP, and TAF9) which, along with the ATPases TIP48 and TIP49, are likely to be involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
136
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(140 citation statements)
references
References 54 publications
(98 reference statements)
4
136
0
Order By: Relevance
“…In the network built by Sardiu and colleagues, NUFIP is shown to be a RPAP3/R2TP/ prefoldin-like complex interactor (Sardiu et al 2008), which is not surprising given that both NUFIP and its yeast homologue, RSA1, where able to bind the R2TP components PIH1D1 (PIH1/Nop17), RUVBL1 (TIP49) and RUVBL2 (TIP48) (McKeegan et al 2007;Boulon et al 2008). In both studies a role for NUFIP and their associated factors in box C/D snoRNP (or even all L7Ae family RNP) biogenesis was proposed.…”
Section: Nufip1mentioning
confidence: 97%
“…In the network built by Sardiu and colleagues, NUFIP is shown to be a RPAP3/R2TP/ prefoldin-like complex interactor (Sardiu et al 2008), which is not surprising given that both NUFIP and its yeast homologue, RSA1, where able to bind the R2TP components PIH1D1 (PIH1/Nop17), RUVBL1 (TIP49) and RUVBL2 (TIP48) (McKeegan et al 2007;Boulon et al 2008). In both studies a role for NUFIP and their associated factors in box C/D snoRNP (or even all L7Ae family RNP) biogenesis was proposed.…”
Section: Nufip1mentioning
confidence: 97%
“…It has been shown that Rvbs and Pih1 as well as Nop56 are co-immunoprecipitated with Nop58 in Hela cells (31). In addition, PIH1D1 depletion resulted in significant decrease of box C/D snoRNAs and accumulation of U3 box C/D snoRNA in Cajal body where snoRNPs transit during its maturation process (31). Furthermore, Su et al showed that snoRNA/snoRNP biogenesis involving RuvBL1/pontin is enhanced in breast cancer (54).…”
Section: Potential Role Of R2tp In Tumorigenesis Through Snornp Pathwaymentioning
confidence: 99%
“…is associated with tumorigenesis. It has been shown that Rvbs and Pih1 as well as Nop56 are co-immunoprecipitated with Nop58 in Hela cells (31). In addition, PIH1D1 depletion resulted in significant decrease of box C/D snoRNAs and accumulation of U3 box C/D snoRNA in Cajal body where snoRNPs transit during its maturation process (31).…”
Section: Potential Role Of R2tp In Tumorigenesis Through Snornp Pathwaymentioning
confidence: 99%
See 2 more Smart Citations